1989
DOI: 10.1017/s0317167100029796
|View full text |Cite
|
Sign up to set email alerts
|

Altered Gene Expression in Alzheimer's Disease Brain Tissue

Abstract: ABSTRACT:We review the evidence for altered gene expression in Alzheimer's disease brain and identify alternative molecular approaches for isolating additional novel markers. One marker, pADHC-9, was isolated from a human hippocampal cDNA library by differential screening with AD and control cDNA probes. This clone hybridizes to a 2 Kb RNA which is increased 2 fold in AD hippocampus. The deduced amino acid sequence of pADHC-9 codes for a 52 kDAL protein similar to a testicular sulfated glycoprotein secreted by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 37 publications
2
27
0
Order By: Relevance
“…Many studies have associated apoJ with AD pathology. In particular, apoJ expression is increased in AD brain [108][109][110] and is present in amyloid plaques and vascular amyloid in AD cortex and hippocampus. [111][112][113][114] ApoJ has been shown to interact with Ab 115-117 and alter its ability to form fibrils [117][118][119] and modifies Abmediated neurotoxicity.…”
Section: Apolipoprotein J-mediated Transport Of Ab Across Bbbmentioning
confidence: 99%
“…Many studies have associated apoJ with AD pathology. In particular, apoJ expression is increased in AD brain [108][109][110] and is present in amyloid plaques and vascular amyloid in AD cortex and hippocampus. [111][112][113][114] ApoJ has been shown to interact with Ab 115-117 and alter its ability to form fibrils [117][118][119] and modifies Abmediated neurotoxicity.…”
Section: Apolipoprotein J-mediated Transport Of Ab Across Bbbmentioning
confidence: 99%
“…(3)). In humans with AD (Duguid et al, 1989;May et al, 1989) and Creutzfeldt Jacob disease (Duguid et al, 1989;) the levels of clusterin mRNA are increased, however, there is no associated increase in clusterin protein levels in AD CSF (Lidstrom et al, 2001) and the level of clusterin protein in CSF is decreased by 2.5 fold in Creutzfeldt Jacob disease (Piubelli et al, 2006). In addition, decreased levels of clusterin in the eye are thought to be responsible for deposition of Pseudo exfoliation (PEX) material in PEX syndrome (Zenkel et al, 2006) (again clusterin is found associated with PEX deposits).…”
Section: When Quality Control Is Compromised?mentioning
confidence: 99%
“…Nucleotide sequence analysis has revealed that pTB16 is homologous to several cDNA sequences cloned from various tissues in different species (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Some in vitro biological properties have been demonstrated for the encoded proteins, such as the induction of Sertoli cell or erythrocyte aggregation (24) and the inhibition or enhancement of hemolysis by the complement terminal complexes (13,25).…”
Section: Resultsmentioning
confidence: 99%
“…Its cDNA was first isolated from cultured Sertoli cells by Collard and Griswold (4). Since that time, many cloned cDNAs from different tissues in various physiological or pathological states were found to be identical to, or a species counterpart of, SGP-2 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Thus, clusterin (8), testosterone-repressed message 2 (TRPM-2) (9), T64 (10), glycoprotein III (11), serum protein 40,40 (12), complement cytolysis inhibitor (13), and pADHC-9 (Alzheimer disease hippocampus clone 9) (14) are all designations for equivalent clones in rodents, birds, ungulates, and humans.…”
mentioning
confidence: 99%